Identification, synthesis and characterization of process related desfluoro impurity of ezetimibe and HPLC method validations - Esen Bellur Atici; Bekir Karlığa (Elsevier, 2015)
Ezetimibe, which selectively inhibits cholesterol absorption across the intestinal wall and is used as an antihyperlipidemic agent, is synthesized for commercial use as a drug substance in highly pure form. During the synthetic process development studies of ezetimibe, an impurity was detected in the final product at levels ranging from 0.05% to 0.15% in reverse phase gradient high performance liquid chromatography (HPLC) method and its molecular weight was determined by LC-MS analysis. The impurity was identified as (3R,4S)-3-((S)-3-(4-fluorophenyl)-3-hydroxypropyl)-4-(4-hydroxyphenyl)-1-phenylazetidin-2-one which is called desfluoro ezetimibe (lactam-related) impurity, synthesized and characterized, the mechanism of its formation was discussed in detail. After all standardization procedures, it was used as a reference standard during validation of HPLC method and routine analyses. In addition, content of Eze-1 desfluoro impurity in Eze-1 intermediates was specified as 0.10% to keep the formation of desfluoro ezetimibe impurity under control and the related substances HPLC method was validated accordingly.